2018
DOI: 10.3892/ol.2018.8218
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-544 promoted human osteosarcoma cell proliferation by downregulating AXIN2 expression

Abstract: microRNAs (miRNAs) perform various oncogenic or tumor suppressor functions in carcinogenesis. Currently, the underlying mechanisms of miRNAs in osteosarcoma (OS) are poorly understood. In the present study, it is demonstrated that expression of miR-544 was markedly upregulated in OS cells and clinical tissues. Furthermore, overexpression of miR-544 enhanced OS cell proliferation in vitro. Bioinformatics analysis indicated that miR-544 may target the 3′-untranslated region of axis formation inhibitor 2, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that miRNA expression is aberrant in ESCC, which suggests that miRNAs play an important role in ESCC progression (6,7). miR-544 was recently demonstrated to function either as a tumor suppressor or oncogene in different types of cancer (8–13,16). However, the expression, function and molecular mechanism of miR-544 in ESCC have not been well illustrated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that miRNA expression is aberrant in ESCC, which suggests that miRNAs play an important role in ESCC progression (6,7). miR-544 was recently demonstrated to function either as a tumor suppressor or oncogene in different types of cancer (8–13,16). However, the expression, function and molecular mechanism of miR-544 in ESCC have not been well illustrated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that miR-544 targets different genes in various cancer types. In osteosarcoma, miR-544 promotes cell proliferation by negatively regulating axin-2 (8). In hepatocellular carcinoma, it enhances immune escape through downregulation of natural cytotoxicity triggering receptor 1/NKp46 by targeting runt-related transcription factor 3 (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between miRNAs and the occurrence and development of tumors has also attracted increasing attention in life science research (14). Researchers have found that miRNAs can regulate the progression of OS (15-17). miR-9 is a member of the miRNA family, and it has been found to be abnormally expressed in a number of types of tumor cells, such as breast cancer, lung cancer, gastric cancer and OS (18-22).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chen et al [10] reported that miR-183 could regulate bladder cancer cells growth and apoptosis via targeting AXIN2. A recent report by Chen et al pointed out that down regulating AXIN2 expression could promote human osteosarcoma cell proliferation [11]. Another paper showed that targeting AXIN2 axis could suppress tumor growth and metastasis in colorectal cancer [12].…”
Section: Introductionmentioning
confidence: 99%